Retrospective Study: Type 1 Leprosy Reaction - Meita Ardini Pratamasari; M. Yulianto Listiawan (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Type 1 reaction (T1R) of leprosy occurs due toaltered balance between cell mediated immunity and M. leprae bacilli in the skin and nerves, with upgrading/reversal or downgrading as final result. Leprosy subpolar types have unstable immunity, this cause them often experience recurrence T1R, especially BB type.Clinical findings of T1R are inflammation in the skin or nerves, and can lead to disability if not treated properly. Aim: To evaluate the distribution, diagnosis, trigger factors, and therapy of T1R. Methods: Retrospective study using medical record of leprosy new patients in Dermatology and Venereology Outpatient Clinic, Dr Soetomo General Hospital, Surabaya, during 2010 – 2013. Database, anamnesis, examination, and T1R therapy were recorded. Results: The total of new leprosy patients with T1R within 2010-2013 were 117 patients (19,7% of all new leprosy patients). Most of them were men (70,1%), aged between 15–34 years (42,8%), with BB as the most frequent type (70,9%). Skin symptom of T1R could be thickening of old lesion (52,1%). T1R most occurred when patients still consume MDT (71,8%). NSAID (37,6%) andcorticosteroid (38,5%)were prescribed as T1R therapy. Conclusions: T1R diagnosis should established accurately by history taking and physical examination.For recurrent T1R,trigger factors should be considered.Key words: type 1 reaction, CMI, reversal, downgrading.